Children's Knowledge of Structure-Dependent Semantic Interactions Between Logical Words. (1st October 2016) - Johnson, Adrienne; Minai, Utako
ABSTRACT: The current study examined preschool children's ability to evaluate the entailment patterns yielded by sentences containing two downward entailing (DE) operators, every and no . When no precedes every, the entailment pattern typically licensed by every changes, but only if no also c-commands every in the hierarchical structure of the sentence. While children had been shown to be sensitive to the effect of a preceding and c-commanding negation on every, it had not been shown whether children were sensitive to the c-command relation between these elements or simply to their linear order. We demonstrate that children's evaluation of the entailment patterns engendered by sentences with no and every makes recourse to hierarchical structural representations. These findings run counter to models positing that young children lack such representations and instead suggest that young children possess both detailed syntactic representations and knowledge of logical operators such as no and every .